2017
DOI: 10.1186/s12885-017-3575-z
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of miRNA-148a and miRNA-625-3p in colorectal cancer is associated with tumor budding

Abstract: BackgroundMiRNAs are often deregulated in colorectal cancer and might function as tumor suppressors or as oncogenes. They participate in controlling key signaling pathways involved in proliferation, invasion and apoptosis and may serve as prognostic and predictive markers. In this study we aimed to evaluate the role of miRNA-148a and miRNA-625-3p in metastatic colorectal cancer.MethodsFifty-four patients with a first-time diagnosed CRC receiving FOLFOX ± Bevacizumab were involved in the study. Tumor samples un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…The protein content and size of bovine milk exosomes was significantly reduced in fermented cow's milk associated with a substantial loss of miRs (miR-29b, miR-21) compared to unfermented raw milk [48]. Malignant epithelial cells of CRC exhibit a reduced Melnik and Schmitz J Transl Med (2019) 17:3 expression of miR-148a [267][268][269][270], which increases the expression of DNMT1 that functions as a tumor promoter in CRC [271][272][273]. Intriguingly, Golan-Gerstl et al [44] demonstrated that the incubation of CRC cells (Lim 1215) with human breastmilk exosomes increased the cellular content of miR-148a.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…The protein content and size of bovine milk exosomes was significantly reduced in fermented cow's milk associated with a substantial loss of miRs (miR-29b, miR-21) compared to unfermented raw milk [48]. Malignant epithelial cells of CRC exhibit a reduced Melnik and Schmitz J Transl Med (2019) 17:3 expression of miR-148a [267][268][269][270], which increases the expression of DNMT1 that functions as a tumor promoter in CRC [271][272][273]. Intriguingly, Golan-Gerstl et al [44] demonstrated that the incubation of CRC cells (Lim 1215) with human breastmilk exosomes increased the cellular content of miR-148a.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Baolei et al revealed that miRNA-124 is a negative regulator of HCC with respect to proliferation and invasion by downregulating lncRNA-UCA1 [35]. Baltruskeviciene E et al found that downregulated expression of miRNA-148a and miRNA-625-3p is related to tumor budding in colorectal cancer, and EMT was considered a possible molecular mechanism [36].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor progression, the final phase of carcinogenesis, is characterized by increased invasiveness and growth ( Jiang et al, 2018 ; Shi et al, 2018 ). Downregulation of miR-148a and miR-625-3p is associated with tumor budding in tumor specimens from 54 patients with a first-time diagnosed colorectal cancer, determined by real-time quantitative (qRT)-PCR ( Baltruskeviciene et al, 2017 ).…”
Section: Mechanisms Of Mir In Colorectal Cancermentioning
confidence: 99%